2005
DOI: 10.1073/pnas.0506410102
|View full text |Cite
|
Sign up to set email alerts
|

Efficient growth inhibition of Bacillus anthracis by knocking out the ribonucleotide reductase tyrosyl radical

Abstract: Bacillus anthracis, the causative agent of anthrax, is a worldwide problem because of the need for effective treatment of respiratory infections shortly after exposure. One potential key enzyme of B. anthracis to be targeted by antiproliferative drugs is ribonucleotide reductase. It provides deoxyribonucleotides for DNA synthesis needed for spore germination and growth of the pathogen. We have cloned, purified, and characterized the tyrosyl radical-carrying NrdF component of B. anthracis class Ib ribonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 40 publications
6
87
3
Order By: Relevance
“…The interaction of S. sanguinis NrdF with its NrdI is also of interest because they belong to a third phylogenetic subgroup that remained uncharacterized until our studies (24,28,51). This subclassification based on bioinformatics is supported by the measured K d of 2.9 M for S. sanguinis NrdI-NrdF interactions, distinct from tighter interactions measured for E. coli (Ͻ0.05 M) and B. subtilis (0.6 M) systems (16).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The interaction of S. sanguinis NrdF with its NrdI is also of interest because they belong to a third phylogenetic subgroup that remained uncharacterized until our studies (24,28,51). This subclassification based on bioinformatics is supported by the measured K d of 2.9 M for S. sanguinis NrdI-NrdF interactions, distinct from tighter interactions measured for E. coli (Ͻ0.05 M) and B. subtilis (0.6 M) systems (16).…”
Section: Discussionmentioning
confidence: 55%
“…This organism can thus also serve as a model for many pathogenic organisms with class Ib RNR as the only aerobic source of deoxynucleotides (27). Fourth, based on phylogenetic analysis (28) 3 H]CDP was obtained from ViTrax and diluted with CDP in buffer A to 6,000 -12,000 cpm/nmol before use. Radioactive samples were analyzed using a Beckman Coulter LS6500 scintillation counter.…”
mentioning
confidence: 99%
“…As discussed above we have previously shown that only the manganese reconstituted form of B. anthracis NrdF shows a substantial enzymatic activity with the physiologically relevant reductants TrxA and NrdH in enzymatic assays (12,13). Additionally, it has been demonstrated that inhibiting B. anthracis RNR using N-methylhydroxylamine efficiently knocks out growth of the organism, making it an attractive target for novel antibiotics (16 (12,15). The FMN content in purified NrdI was determined via acid treatment of the protein to release the FMN cofactor, in accordance with the method of Mayhew and Massey (17).…”
Section: Ribonucleotide Reductases (Rnrs)mentioning
confidence: 99%
“…Preparation and Characterization of Mn-reconstituted B. anthracis NrdF-The apo-NrdF protein was purified via a modified literature procedure (16), by adding an incubation with 5 mM EDTA under reducing conditions for 2-3 h after which time adventitiously bound metal ions were removed by sizeexclusion chromatography. Finally, apo-NrdF was isolated in Ͼ95% purity by anionic exchange chromatography.…”
Section: Isolation and Characterization Of B Anthracis Nrdi-whenmentioning
confidence: 99%
See 1 more Smart Citation